Unleashing the Power of Clustering: Enhancing Descriptive Text Writing through Innovative Teaching Techniques - Laila Inggil Hikmawati; Ngasbun Egar; Siti Musarokah (Journal of English Education Program, 2023)
This research delves into students' writing abilities, emphasizing the impact of utilizing clustering techniques in teaching descriptive text. The study aims to achieve three objectives: firstly, to assess the writing proficiency of students instructed without clustering techniques; secondly, to gauge the writing proficiency of students taught using clustering techniques; and thirdly, to determine the significant disparity in writing abilities between these two teaching methods. Employing a quasi-experimental quantitative design with pre- and post-tests, the research involves two distinct groups: one exposed to the clustering approach and the other to traditional instruction. Junior high school students in Semarang serves as the research setting, encompassing class VIII students. Data collection spanned eight sessions and encompassed pre-tests, treatment, and post-tests. The experimental group comprised 31 students, while the control group had 32 students. Analysis of the pre- and post-test results revealed noteworthy insights. Students in the control group exhibited a marginal decrease in average scores, from an initial 62.34 to 60.59, following conventional instruction. This contrasts with the experimental group, where clustering techniques potentially facilitated a more positive trajectory in writing skills. The study underscores the potential benefits of integrating clustering methods in teaching descriptive text, potentially enhancing students' written expression capabilities.